Article Title Article Title Pattern analysis using fuzzy VIKOR in locating educational facilities district Case Study: District 14 of Tehran Metropolis - behnaz amin nayeri; yaghoub peyvastehgar (تحقیقات کاربردی علوم جغرافیایی)
With the increasing population in cities, particularly big cities, demand for public goods and services increased too. But, due to certain political-economic structure of the country, often the rates of supplies growth have been less than the demands’. The high-demand applications such as educational, for many reasons including, Lack of cities’ coordination executive bodies, financial problems and lack of education sector officials with scientific procedures for locating schools, faced with many problems to meet the needs of the students. In large urban areas like Tehran, for various reasons such as high population density and scarcity of land, these problems intensified. Fast, timely and appropriate accessibility to these training centers is very important and necessary in every community, especially in urban areas. And the equitable distribution of these centers in the city led to the establishment of spatial equity and social justice, which is an urban sustainable development objectives. The aim of this research is to evaluate the locating of training centers in primary schools in the district in order to achieve spatial justice. The type of research is practical, based on the purpose of thstudy, and the research method is descriptive-analytic. The data collection method is also documentary-survey. In order to weigh the criteria, experts have been used in the ANP model, and by Using the capabilities and features of geographical information system including: combining maps, raster calculator, network analysis and etc. has been done. Finally, after the implementation of VIKOR sample, the priority areas were identified for building elementary schools. The final output analysis obtained by this method in addition to determining of the compatibility or incompatibility of primary schools in the city will located the optimal sites for building new elementary schools.